Antioxidant system breakdown in brain of feral golden grey mullet (Liza aurata) as an effect of mercury exposure - Mieiro, C. L.
Although brain has been recognized as a primary target for mercury toxicity in mammals, the effects of this metal in fish brain are scarcely described. Thus, the main objective of this study was to assess the mercury threat to feral fish (Liza aurata) by estimating the antioxidant defenses and peroxidative damage in brain, keeping in mind the association with mercury accumulation. Sampling was carried out in an estuarine area historically affected by discharges from a chlor-alkali industry—Laranjo Basin (Ria de Aveiro, Portugal). Total mercury (T-Hg) in brain increased towards the contamination source, clearly indicating mercury exposure. An overall antioxidant depletion was verified in brain of fish collected at the mercury-contaminated stations, since total glutathione content and the studied antioxidant enzymes (catalase—CAT, glutathione peroxidase—GPx, glutathione-S-transferase—GST and glutathione reductase—GR) significantly decreased. In addition, this breakdown of the redox-defense system was significantly correlated with the accumulated T-Hg levels. Unexpectedly, fish exhibited unaltered lipid peroxidation levels, pointing out a higher propensity of mercury to inhibit enzymes than to oxidatively damage lipids in the brain. Nevertheless, an increased susceptibility of the fish’s brain was identified, leaving the organ more vulnerable to oxidative stress-related challenges. Overall, the current findings provide information to better understand mechanisms of mercury neurotoxicity in fish.